APPLICATION OF ISO/IEC 9126 ON QUALITY MEASUREMENT OF WEB-BASED RECORDS MANAGEMENT APPLICATIONS AT ITCC ITPLN - Hendra Jatnika; M. Farid Rifai; Vincentia Reynada Primadhani (Sean Institute, 2023)
The International Technology Certification Center (ITCC) is one of the implementing agencies of certification at ITPLN to support certification activities in the IT field. In managing the archives, it still use a conventional system so that it has several weaknesses, among others: making the archive management system less effective, less efficient in terms of time, cost, energy, and storage space for archives, lack of security in storing documents, and maintaining documents requires more cost and time. Therefore, a web-based archive management application is designed to overcome these weaknesses. User Centered Design (UCD) method is used in developing this system and ISO / IEC 9126 as testing the software quality using 6 aspects. Testing the quality of the ITCC Archive Management Application received 97,61% results (Very Good).